2007
DOI: 10.1111/j.1600-079x.2007.00540.x
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin, consciousness, and traumatic stress

Abstract: :  Descartes intuitively anticipated the so‐called ‘binding problem’ of consciousness and thought that the pineal gland enables spatio‐temporal integration in cognitive processing. Recent findings indicate that a major role in the process of temporal integration and binding involve neurons in suprachiasmatic nuclei, specifically targeting the pineal gland and other structures, and control the neuroendocrine rhythms. Melatonin is an endocrine output signal of the clock and provides circadian information as an e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
29
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(29 citation statements)
references
References 121 publications
0
29
0
Order By: Relevance
“…128 Long-term potentiation is a measure that results from simultaneous activity between 2 neurons, enhancing the signal neurotransmission after electrical stimulation. 128 As reviewed by Bob and Fedor-Freybergh, 129 MLT regulates memory formation, acting directly on hippocampal neur ons, 29,130 which are involved in the processes of memory acquisition and consolidation. [131][132][133] In particular, MLT enhances the firing rate of action potentials in CA 1 neurons of hippocampal slices 29 and promotes synaptic transmission.…”
Section: Mt 2 Receptor Memory Function and Alzheimer Diseasementioning
confidence: 99%
“…128 Long-term potentiation is a measure that results from simultaneous activity between 2 neurons, enhancing the signal neurotransmission after electrical stimulation. 128 As reviewed by Bob and Fedor-Freybergh, 129 MLT regulates memory formation, acting directly on hippocampal neur ons, 29,130 which are involved in the processes of memory acquisition and consolidation. [131][132][133] In particular, MLT enhances the firing rate of action potentials in CA 1 neurons of hippocampal slices 29 and promotes synaptic transmission.…”
Section: Mt 2 Receptor Memory Function and Alzheimer Diseasementioning
confidence: 99%
“…Hippocampal neurons have receptors for melatonin (Morgan et al, 1994;Musshoff et al, 2002), and the administration of this hormone is known to alter excitability and synaptic transmission within the hippocampus (Hogan et al, 2001;Musshoff et al, 2002;Wan et al, 1999), and melatonin has been shown to alter hippocampal synaptic plasticity through the MT2-mediated regulation of the adenylate cyclase-protein kinase A (AC-PKA) pathway (Wang et al, 2005). The synaptic plasticity in the hippocampus and other brain regions has recently gained attention as an important means by which melatonin may augment its neuroprotective effects beyond reductions in oxidative stress alone (Baydas et al, 2005;Bob and Fedor-Freybergh, 2008;Fukunaga et al, 2002;Gorfine and Zisapel, 2007;Larson et al, 2006;Talaei et al, 2009;Wang et al, 2005). In light of these findings, and those of this study, there is an urgent need for more high-quality mechanistic studies to further investigate these plasticity processes as a possible means of improving outcomes after ICH.…”
mentioning
confidence: 99%
“…The SCN comprises individual neuronal oscillators coupled into a neural network. First it was thought that the SCN was composed of identical resettable oscillators, however, more recent investigations have shown that circadian rhythmicity in the SCN is the product of a highly organized network of heterogeneous cells [ 4 ].…”
Section: Circadian Synchronization Of Cognitive Functionsmentioning
confidence: 99%